Mesenchymal stem cells promote CD206 expression and phagocytic activity of macrophages through IL-6 in systemic lupus erythematosus - Deng, Wei (Clinical immunology (Orlando, Fla.), 2015)
Copyright © 2015 Elsevier Inc. All rights reserved.